Reform Realism and the Boardroom - World Bank (World Bank, Washington, DC, 2012)
The board of a 21st century corporation has the imperative to navigate the shoals of regulatory landmines without making a shipwreck of its entrepreneurial energy and strategic thrusts, aptly summarizing one major challenge for directors. Having in place effective corporate governance best practices and training directors to understand their duties are essential steps in improving the sustainability of companies. One principle is that a board can delegate, but it cannot abdicate its responsibilities. This speaks to the fundamental division between the board's role, that of strategic direction, and management's duty of executing the board's strategy. The board must monitor management's performance, even though it does not directly carry out the actions. As Koh notes, courts have rejected the argument that a lower standard of care should apply to non-executive directors than to executive directors.